Chapter Manufacturing Engineering (A Review on Intelligence STEP-NC Data Model and Function Blocks CNC Machining Protocol) - Mohamed, Prof. Ts. Dr. Saiful Bahri (Trans Tech Publications Ltd, 2014)
This review paper describes the implementation process for STEPNCFBUoA. Its software environment is first explained. ST-Developer is the central software tool that is responsible for converting EXPRESS schema to Java classes. FBDK is the tool used for developing the function blocks editor, raw material user interface, machining set-up data interface, and machine tool database. The two examples in the ISO 14649-11 standard are used as the main test parts. The paper provides a detailed account of STEP-NC data processing, Graphic user interface (GUI) and local manufacturing databases, for example, raw material, set-up, machine tool, and cutting tool databases. Machining simulation is validated through physical machining. This is done through machining a number of parts with varying data. The simulation graphic user interface is simple and wire-frame based, but sufficiently illustrates the tool-path information as well as showing the machine tool’s limits, and set-up orientations.